LAYERED MANTLE STRUCTURE BENEATH THE WESTERN GUYANA SHIELD, VENEZUELA: EVIDENCE FROM DIAMONDS AND XENOCRYSTS IN GUANIAMO KIMBERLITES - Schulze D.J.; Canil D.; Channer D.M.De.R.; Kaminsky F.V. (My University, 2006)
Mantle xenoliths and xenocrysts from Guaniamo, Venezuela kimberlites record equilibration conditions corresponding to a limited range of sampling in the lithosphere (100-150 km). Within this small range, however, compositions vary considerably, but regularly, defining a strongly layered mantle sequence. Major and trace element compositions suggest the following lithologic sequence: highly depleted lherzolite from 100 to 115 km, mixed ultra-depleted harzburgite and lherzolite from 115 to 120 km, relatively fertile lherzolite from 120 to 135 km, and mixed depleted harzburgite and relatively fertile lherzolite from 135 to 150 km. Based on comparison with well-documented mantle peridotites and xenocrysts from elsewhere, we conclude that the Meso-proterozoic Cuchivero Province (host to the Guaniamo kimberlites) is underlain by depleted and ultra-depleted shallow Archean mantle that was underplated, and uplifted, by Proterozoic subduction, perhaps more than once. These Proterozoic subduction events introduced less-depleted oceanic lithosphere beneath the Archean section, which remains there and is the source of the abundant Guaniamo eclogite-suite diamonds that have ocean-floor geochemical signatures. Although diamond-indicative low-Ca Cr-pyrope garnets are abundant, they are derived primarily from the shallow depleted layer within the field of graphite stability, and the rare peridotite-suite diamonds are either metastably preserved at these shallow depths, or were derived from the small amount of depleted lithosphere sampled by these kimberlites that remains within the diamond stability field (the mixture of Archean and Proterozoic mantle in the depth range 135-150 km). © 2005 Elsevier Inc. All rights reserved.
Keywords: Proterozoic; Archean; Precambrian::Proterozoic; Докембрий::Протерозой; Precambrian::Archean; Докембрий::Архей